Decentralized Autonomous Organizations: A new contribution of Legaltech in the commercial sector? - Yarlequé Marcelo, Gabriela (2022)
The rise of new technologies has had a significant impact on various sectors and the legal field has been no exception for digital transformation. The application of these technological tools in the legal sector is known as Legaltech. The constant development of programming for the benefit of the business sector has been reflected in the emergence of a type of organizations known as Decentralized Autonomous Organizations (DAOs). These organizations have their bases in Blockchain technology and Smart Contracts, as well as other technologies in the field of Distributed Ledger Technology (DLT). The systematization of the operations carried out in DAOs brings with it advantages over traditional trading or capital companies. Their exponential increase worldwide poses a series of challenges in the legal field; therefore, it is important to analyze whether it is convenient to implement a legal regulation in relation to DAOs and their main limitations in Peru.